Adapting and/or adopting non-authentic and genuine materials for an ERP context, towards a stereotype-free thinking English - N LABED (Revue des Sciences Humaines)
Language teachers have understood that to enliven the classroom they needed to teach realism ; thus they needed real-life materials.